Milk Consumption Frequency and Bone Mineral Density Z-scores In Women Aged 20–35 Years: A Cross-sectional Study - Siti Ramadhoni Al Rasyid (Jurnal Imejing Diagnostik (JImeD), 2026)
Background: Optimizing peak bone mass in early adulthood is important for long-term skeletal health. Milk provides calcium and high-quality protein that may support bone mineral density (BMD). However, evidence regarding the association between milk consumption and BMD in young adult women, particularly in non-Western populations, remains limited. This study aimed to assess whether milk consumption frequency is associated with BMD Z-scores in women aged 20–35 years. Methods:  An analytical observational study with a cross-sectional design was conducted among 60 premenopausal women aged 20–35 years. Milk consumption frequency was categorized as non-consumers, 1–3 times/week, and >3 times/week. Lumbar spine (L1–L4) and femoral neck BMD were measured using Dual-Energy X-ray Absorptiometry (DXA) and expressed as Z-scores. Normality was assessed prior to analysis, and One-way ANOVA was used to compare mean Z-scores across groups (α = 0.05), with additional sensitivity analysis using non-parametric testing due to imbalance in group sizes Results:  Mean (SD) Z-scores were 0.068 (0.927) for lumbar spine and −0.528 (0.797) for femoral neck. There was no significant difference in lumbar spine Z-scores across milk consumption groups F (2.57) = 0.479; p = 0.622). Similarly, femoral neck Z-scores were not significantly different F (2.57) = 2.673; p = 0.078), although a trend toward higher Z-scores was observed among participants with more frequent milk consumption. Conclusions:  In this sample of women aged 20–35 years, milk consumption frequency was not significantly associated with lumbar spine or femoral neck BMD Z-scores. These findings suggest that milk consumption alone may be insufficient to influence BMD in this population without considering other determinants such as total calcium intake, vitamin D status, and physical activity. Further studies with larger, more balanced samples and improved control of potential confounders are warranted.